DeltaE modelling and experimental study of a standing wave thermoacoustic test rig - Mohd Saat, Fatimah Al Zahrah; Johari, Dahlia; Mat Tokit, Ernie (Penerbit Akademia Baru, 2019)
Thermoacoustics is a principle of sciences that could be used to create an alternative green and sustainable technology for a cooler or a generator. Unfortunately, the fluid dynamics of the oscillatory flow within thermoacoustic environment is less understood especially as the flow conditions change to higher values of operating conditions. This leads to difficulties in design practices of the system. In this paper, a test of an experimental rig for the investigation of fluid dynamics of an oscillatory flow inside a standing-wave thermoacoustic rig with two different flow frequencies are reported. An experimental setup was build and numerical modelling is also solved using a thermoacoustic software known as DeltaE. The rig consisted of a quarter wavelength resonator attached to a loudspeaker that acts as an acoustic driver. A structure known as ‘stack’ is located at a location of approximately 0.19 from the pressure antinode. Experimental results showed that the resonance frequency of the two setups are 14.2 Hz and 23.6 Hz, respectively. Measured velocity and pressure at several locations are analysed and the results indicated that the thermoacoustic flow conditions are achieved. The rig could be used for further and deeper investigations of fluid dynamics behaviour for oscillatory flow of thermoacoustics